Caring for both ‘Inside’ and ‘Outside’ Hotel Clients in Terms of Total Quality Management Philosophy - Broniewska, Grażyna (Turyzm/Tourism, 2003)
The article is based on the Total Quality Management (TQM) philosophy assumption that “By satisfying the inside client's needs as fully as possible, we can equally satisfy the outside client’s needs". The author highlights the key role of the involvement and satisfaction on the part of hotel personnel in achieving the goals of the firm by giving examples from actual hotels.